Prediction of cure and risk of hypothyroidism in patients receiving 131I for hyperthyroidism. - Boelaert, K; Syed, A; Manji, N; Sheppard, M; Holder, R; Gough, S; Franklyn, J (2009)
CONTEXT: There is little consensus regarding the most appropriate dose of radioiodine ((131)I) to be administered to patients with hyperthyroidism. OBJECTIVE: To compare the efficacy of fixed dose regimens of (131)I in curing hyperthyroidism and to define simple clinical and biochemical factors that predict outcome in individual patients. DESIGN: Consecutive series of hyperthyroid subjects treated with (131)I. SETTING: Single Secondary/Tertiary Care Hospital Clinic. PARTICIPANTS: A total of 1278 patients (1013 females and 262 males, mean age 49.7 years) presenting with hyperthyroidism between 1984 and 2006. INTERVENTION: Treatment with (131)I using a fixed dose regimen. MAIN OUTCOME MEASURES: Probability of cure and risk of development of hypothyroidism following a single dose of (131)I. RESULTS: Patients given a single dose of (131)I of 600 MBq (n = 485) had a higher cure rate (84.1%) compared with those receiving either 370 MBq (74.9%, P < 0.001) or those given 185 Bq (63%, P < 0.001). An increased incidence of hypothyroidism by 1 year was evident with higher doses (600 MBq: 60.4%; 370 MBq: 49.2%, P = 0.001; 185 Bq: 38.1%, P < 0.001). Binary logistic regression analysis identified a 600 Bq dose of (131)I [adjusted odds ratio, AOR 3.33 (2.28-4.85), P < 0.001], female gender [AOR 1.75 (1.23-2.47), P = 0.002], lower presenting serum free T4 concentration [AOR 1.01 (1.01-1.02), P < 0.001] and absence of a palpable goitre [AOR 3.33 (2.00-5.56), P < 0.001] to be independent predictors of cure. Similarly, a 600 MBq dose [AOR 3.79 (2.66-5.38), P < 0.001], female gender [AOR 1.46 (1.05-2.02), P = 0.02], younger age [AOR 1.03 (1.02-1.04), P < 0.001], absence of a palpable goitre [AOR 3.85 (2.38-5.88), P < 0.001] and presence of ophthalmopathy [AOR 1.57 (1.06-2.31), P = 0.02] were identified as independent factors predicting the probability of development of hypothyroidism at one year. Based on these findings, formulae to indicate probability of cure and risk of hypothyroidism for application to individual patients were derived. CONCLUSIONS: Simple clinical/biochemical criteria can be used to predict outcome after (131)I treatment. These factors determine that males, those with severe biochemical hyperthyroidism, and those with a palpable goitre require larger doses (600 MBq) in order to achieve cure.